MANAJEMEN BANK SAMPAH CEMARA MELALUI INOVASI PRODUK DAUR ULANG LIMBAH PLASTIK DAN PENGELOLAAN MANAJEMEN USAHA - Risnawati Risnawati; Novica Indrianty; Satriadi Satriadi (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The "Cemara" waste bank was established on November 24, 2023, located in Kp. Kolong Enam RT 003 RW 022 Kel. Kijang Kota, East Bintan District, Bintan Regency. The main objectives of this service program include: (1) identifying the problems and needs of the "Cemara" waste bank (2) providing solutions based on the identification of problems that exist in the "Cemara" waste bank (3) to increase community participation in the activities of the "Cemara" waste bank (4) increasing the benefits of the "Cemara" waste bank. The partner in the activity is the "Cemara" waste bank, managed by Akbar, located in Kp. Kolong Enam RT 003 RW 022 Kel. The stages of this program include socialization, training, technology application, mentoring and evaluation, and program sustainability. The results of the evaluation showed that the majority of participants, as many as 80%, understood the stages of the activity very well, with 80% understanding, and 20% adequately understanding the material presented